Intracranial Aneurysms: Review of Current Treatment Options and Outcomes - Seibert, Brad; Tummala, Ramachandra; Chow, Ricky; Faridar, Alireza; Mousavi, Seyed A.; Divani, Afshin A. (Frontiers in Neurology, 2011)
Intracranial aneurysms are present in roughly five percent of the population, yet most are often asymptomatic and never detected. Development of an aneurysm typically occurs during adulthood, while formation and growth are associated with risk factors such as age, hypertension, pre-existing familial conditions, and smoking. Subarachnoid hemorrhage, the most common presentation due to aneurysm rupture, represents a serious medical condition often leading to severe neurological deficit or death. Recent technological advances in imaging modalities, along with increased understanding of natural history and prevalence of aneurysms, have increased detection of asymptomatic unruptured intracranial aneurysms. Studies reporting on the risk of rupture and outcomes have provided much insight, but the debate remains of how and when unruptured aneurysms should be managed. Treatment methods include two major intervention options: clipping of the aneurysm and endovascular methods such as coiling, stent-assisted coiling, and flow diversion stents. The studies reviewed here support the generalized notion that endovascular treatment of unruptured intracranial aneurysms provides a safe and effective alternative to surgical treatment. The risks associated with endovascular repair are lower and incur shorter hospital stays for appropriately selected patients. The endovascular treatment option should be considered based on factors such as aneurysm size, location, patient medical history, and operator experience.